Comparison of effectiveness and cost in handling bagworm attack using trunk injection and machine sprayer at Felcra Seberang Perak / Mohamad Syazwan Mohamed Annuar - Mohamed Annuar, Mohamad Syazwan (Faculty of Plantation and Agrotechnology, 2017)
This study was conducted to determine and compare which treatment is more effective between trunk injection and the machine sprayer to control and handling bagworm attack. Also, this study objective also to determine which technique is cheaper and less in term of costing to handling the bagworm attack in the field. The difference in technology used in handling to control the bagworm attack in the field will give a huge impact in term of production and profit in the future and give a huge impact in costing management involve to prevent the bagworm attack not more than economic threshold level (ETL). From this study, we can determine which method can give large impact to controlling bagworm attack with less costing of handling the bagworm attack to be used by the oil palm plantation sector. In order to determine the method successfully, data collection, such as cencus in total number of pupa and larva before and after the treatment and total costing of management in handling bagworm attack for trunk injection and machine sprayer. Then the result will be interpreted in SPSS software (version 22) to determine the significance of effect before and after the treatment involved from two different methods. In addition, based from this study, estate management can determine and find the best way to use in handling the bagworm attack by effectiveness of treatment and the cost of handling the treatment.